2019
DOI: 10.1515/cclm-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Large platelet size is associated with poor outcome in patients with metastatic pancreatic cancer

Abstract: Background Platelets are a major cellular component of blood and their interaction with cancer cells is well-established to influence cancer progression and metastases. The physical size of platelets may have a critical impact on the interaction with cancer cells. In this study, we explored the potential prognostic role of platelet size measured by the determination of the mean platetlet volume (MPV) in patients with pancreatic ductal adenocarcinoma (PDAC). Methods Data from 527 patients with PDAC diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Furthermore, the high level of MPV corresponds to the worse course of the disease in pancreatic cancer. Study of Lembeck et al [14] showed that patients with high MPV were more likely to have high-grade G3/4 tumors (p = 0.004). Moreover, they had lower average PLT, higher average bilirubin levels, and higher CRP levels.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, the high level of MPV corresponds to the worse course of the disease in pancreatic cancer. Study of Lembeck et al [14] showed that patients with high MPV were more likely to have high-grade G3/4 tumors (p = 0.004). Moreover, they had lower average PLT, higher average bilirubin levels, and higher CRP levels.…”
Section: Introductionmentioning
confidence: 96%
“…In multivariable analysis, the adverse association between large platelets and a higher risk-of-death prevailed in metastatic stage IV patients, but not in patients with early/locally advanced disease [14]. Furthermore, in patients with pancreatic ductal adenocarcinoma (PDAC), a large platelet volume is associated with high-grade G3/4 tumors (p = 0.004) and worse OS in patients with metastatic disease in univariable analysis (p = 0.005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of MPV seems to have prognostic value in many types of solid tumorscolorectal cancer, gastric cancer, renal cell carcinoma, esophageal cancer, non-small cell lung cancer, invasive breast cancer or papillary thyroid carcinoma. [4][5][6][7][8][9][10][11] Single reports on the role of MPV in lymphoproliferative diseases could also be found in the literature. Low MPV values were related to worse outcome in patients with diffuse large B-cell lymphoma (DLBCL).…”
Section: Introductionmentioning
confidence: 99%
“…Larger platelets store more granules and receptors, and adhere faster than smaller platelets. Therefore, the activity of platelets is more accurately expressed by their size than by counting (11)(12)(13). The ratio of platelet distribution width to platelet count is a commonly used measurement of platelet size and an alternative indicator of platelet activation (14).…”
Section: Introductionmentioning
confidence: 99%